2023
DOI: 10.3390/ph16071021
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Green Tea Catechins in Hematological Malignancies

Abstract: Green tea catechins are bioactive polyphenol compounds which have attracted significant attention for their diverse biological activities and potential health benefits. Notably, epigallocatechin-3-gallate (EGCG) has emerged as a potent apoptosis inducer through mechanisms involving caspase activation, modulation of Bcl-2 family proteins, disruption of survival signaling pathways and by regulating the redox balance, inducing oxidative stress. Furthermore, emerging evidence suggests that green tea catechins can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 124 publications
0
11
0
Order By: Relevance
“…EGCG has become an important pathway for epigenetic therapy for leukemia and MDS, and it also has synergies when used in combination with conventional chemotherapy drugs (Della Via et al, 2023). In addition, in phase Ⅱ double-blind, placebocontrolled randomized clinical trial, preventive use of EGCG solution significantly reduced the incidence and severity of RID in patients with adjuvant radiotherapy for breast cancer (Zhao et al, 2022).…”
Section: Non-nucleoside Inhibitorsmentioning
confidence: 99%
“…EGCG has become an important pathway for epigenetic therapy for leukemia and MDS, and it also has synergies when used in combination with conventional chemotherapy drugs (Della Via et al, 2023). In addition, in phase Ⅱ double-blind, placebocontrolled randomized clinical trial, preventive use of EGCG solution significantly reduced the incidence and severity of RID in patients with adjuvant radiotherapy for breast cancer (Zhao et al, 2022).…”
Section: Non-nucleoside Inhibitorsmentioning
confidence: 99%
“…Originating from China, tea was introduced to the world thousands of years ago via the Silk Road. The production of green tea involves decoction or steaming of freshly harvested leaves to inactivate polyphenol oxidase and other enzymes that prevent fermentation/oxidation, preserving the active chemical properties [ 92 ]. As one of the most consumed beverages worldwide, green tea has been the focus of much research, and its polyphenolic compounds have been shown to have many benefits for human health.…”
Section: Natural Medicines With Therapeutic Potential For Aplmentioning
confidence: 99%
“…Catechins are inexpensive, safe, and can be administered orally. Catechins, especially EGCG, have multifaceted effects that make them attractive candidates for the prevention and treatment of leukemia and myelodysplastic syndrome [ 92 , 93 ].
Fig.
…”
Section: Natural Medicines With Therapeutic Potential For Aplmentioning
confidence: 99%
See 1 more Smart Citation
“…It also been reported that EGCG inhibit the angiogenesis, induce epigenetic modifications, carcinogenesis, and metastasis in animal models (17,18) . Plenty of reports in animals, as well as case-control and epidemiologic studies in humans, reveal that green tea consumption or oral administration for long-term significantly reduces the incidence of various cancers (19,20) , indicated a vital role of EGCG in the chemoprevention of cancer. The large number reports suggested the excellent anticancer potency of EGCG alone as well as along other compounds or drugs, however the specific binding target for EGCG is not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%